Ever-Changing MRLs for Fresh Citrus Exports - Ritenour, Mark A (EDIS, 2022)
This article explains the concept of maximum residue limits, their importance for successfully marketing fresh citrus (esp. for exports), and how to find current maximum residue tolerances for the United States and important export markets on materials used for growing and packing fresh Florida citrus.